Palestrina in Serbia - Moody, Ivan (Muzikološki zbornik, 2020)
Kosta P. Manojlović was a highly significant figure in the development of Serbian choral music and musical education. His studies abroad brought him into contact with repertoires of Western "early music" that had a profound impact on his work. This article discusses his adaptations of Renaissance polyphony found in the archive of the First Belgrade Choral Society.
Keywords: choral music; early music; glasbene priredbe; Manojlović, Kosta P.; music arrangement and adaptation; polifonija; polyphony; Serbian composers; srbski skladatelji; stara glasba; zborovska glasba